2015
DOI: 10.1080/15374416.2015.1041594
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Alliance With Depressed Adolescents: Predictor or Outcome? Disentangling Temporal Confounds to Understand Early Improvement

Abstract: Psychotherapy research reveals consistent associations between therapeutic alliance and treatment outcomes in the youth literature; however, past research frequently suffered measurement issues that obscured temporal relationships between alliance and symptomatology by measuring variables later in therapy, thereby precluding examination of important early changes. The current study aimed to explore the directions of effect between alliance and outcome early in therapy with adolescents by examining associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 59 publications
2
27
0
1
Order By: Relevance
“…In youth psychotherapy, only a handful of studies has controlled for pre-treatment symptom severity or prior symptom change in the estimation of the alliance-outcome association. The few studies that controlled for initial severity found evidence for an association between early alliance and subsequent improvement at mid-treatment in cognitivebehavioural therapy (CBT) for young people with depression (Labouliere, Reyes, Shirk, & Karver, 2017) and anxiety disorders (Chiu et al, 2009). The empirical evidence on the allianceoutcome relationship while controlling for prior symptom change is scant and present mixed results.…”
Section: Temporal Relationships Between Alliance and Symptomatic Changementioning
confidence: 99%
“…In youth psychotherapy, only a handful of studies has controlled for pre-treatment symptom severity or prior symptom change in the estimation of the alliance-outcome association. The few studies that controlled for initial severity found evidence for an association between early alliance and subsequent improvement at mid-treatment in cognitivebehavioural therapy (CBT) for young people with depression (Labouliere, Reyes, Shirk, & Karver, 2017) and anxiety disorders (Chiu et al, 2009). The empirical evidence on the allianceoutcome relationship while controlling for prior symptom change is scant and present mixed results.…”
Section: Temporal Relationships Between Alliance and Symptomatic Changementioning
confidence: 99%
“…The therapeutic relationship has long been emphasized as a critical element in both adult and youth psychotherapies (Labouliere, Reyes, Shirk, & Karver, ). It is largely accepted that the therapeutic relationship refers to the feelings and attitudes that therapist and client have toward one another, and the manner in which these are expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have generally, recommended special consideration of the development of alliance in therapies with adolescents and younger adults [71,72]. In the extraordinary situation of the present study, the trusting relationship seemed more insecure or easily disrupted in the younger age group.…”
Section: Young Adults Were More Vulnerablementioning
confidence: 56%